Kegiatan edukasi kesehatan mental berbasis e-booklet untuk meningkatkan pengetahuan dan menurunkan kecemasan akademik remaja - Rafika Dora Wijaya; Agnes Defvi Romayanti Simarmata; Rohanah Rohanah; Muayah Muayah; Siti Fadillah (JOURNAL of Public Health Concerns, 2026)
Background: Adolescent mental health is a crucial aspect that influences students' learning process, social development, and quality of life. One common problem experienced by adolescents is academic anxiety due to study pressure, grade demands, and the burden of schoolwork. Low mental health literacy among adolescents results in students lacking understanding of how to manage academic stress healthily. Purpose: To increase mental health knowledge and reduce academic anxiety through an e-booklet-based educational program for students. Method: The program was implemented in 2025 at SMK PGRI Balaraja Tangerang, involving 105 vocational high school students as respondents. The goal was to provide literacy about mental health and academic anxiety levels to students. The program used an educational and participatory approach consisting of preparation, implementation, and evaluation stages. Education was delivered through interactive lectures, discussions, Q&A sessions, and relaxation technique simulations using an e-booklet accessed via students' smartphones. Evaluation used a pre-test and post-test to measure students' levels of academic knowledge and anxiety before and after the intervention. The evaluation results were analyzed using the Wilcoxon test and presented descriptively regarding the increase in mental health literacy and changes in respondents' levels of academic anxiety. Results: The majority of students (92 respondents, 87.6%) were 17 years old, with 57 respondents (54.3%) being female. The results of the activity showed an increase in students' knowledge, categorized as good, from 17.1% to 74.3%. Furthermore, the level of high academic anxiety decreased from 25.8% to 4.7% after receiving e-booklet-based mental health education. Conclusion: E-booklet-based mental health education is effective in increasing students' knowledge and reducing academic anxiety in adolescents. The e-booklet is considered effective because it is easily accessible, engaging, and can be independently reviewed by students. This program can be a promotional and preventive effort to increase mental health literacy and reduce academic anxiety in school adolescents. Suggestion: Schools are expected to continue regular mental health education programs through activities and counseling to help students understand the importance of maintaining mental health. Teachers and other educational staff are also expected to be more active in providing psychological support to students experiencing academic anxiety. Keywords: Academic anxiety; E-booklet; Health education; Knowledge; Teenager Pendahuluan: Kesehatan mental remaja merupakan aspek penting yang memengaruhi proses belajar, perkembangan sosial, dan kualitas hidup siswa. Salah satu masalah yang sering dialami remaja adalah kecemasan akademik akibat tekanan belajar, tuntutan nilai, dan beban tugas sekolah. Rendahnya literasi kesehatan mental pada remaja menyebabkan siswa kurang memahami cara mengatasi stres akademik secara sehat. Tujuan: Untuk meningkatkan pengetahuan kesehatan mental dan menurunkan kecemasan akademik melalui program edukasi berbasis e-booklet pada siswa. Metode: Kegiatan dilaksanakan pada tahun 2025 di SMK PGRI Balaraja Tangerang dengan melibatkan 105 siswa/siswi SMK untuk menjadi responden. Sasarannya adalah pemberian literasi tentang kesehatan mental dan tingkat kecemasan akademik pada siswa. Pelaksanaan kegiatan menggunakan pendekatan edukatif dan partisipatif yang terdiri dari tahap persiapan, implementasi, dan evaluasi. Edukasi dilakukan melalui ceramah interaktif, diskusi, tanya jawab, serta simulasi teknik relaksasi menggunakan media e-booklet yang diakses melalui smartphone siswa. Evaluasi dilakukan menggunakan pre-test dan post-test untuk mengukur tingkat pengetahuan dan kecemasan akademik siswa sebelum dan sesudah intervensi. Hasil evaluasi di analisa Wilcoxon test dan disampaikan secara deskriptif mengenai peningkatan literasi kesehatan mental dan perubahan tingkat kecemasan akademik responden.  Hasil: Menunjukkan bahwa mayoritas siswa berusia 17 tahun yaitu sebanyak 92 responden (87.6%), sebagian besar responden berjenis kelamin perempuan sebanyak 57 responden (54.3%) Hasil kegiatan menunjukkan adanya peningkatan pengetahuan siswa kategori baik dari 17.1% menjadi 74.3%. Selain itu, tingkat kecemasan akademik kategori tinggi menurun dari 25.8% menjadi 4.7% setelah diberikan edukasi kesehatan mental berbasis e-booklet. Simpulan: Edukasi kesehatan mental berbasis e-booklet efektif dalam meningkatkan tingkat pengetahuan siswa dan menurunkan kecemasan akademik pada remaja. Media e-booklet dinilai efektif karena mudah diakses, menarik, dan dapat dipelajari kembali secara mandiri oleh siswa. Program ini dapat menjadi salah satu upaya promotif dan preventif dalam meningkatkan literasi kesehatan mental serta menurunkan kecemasan akademik pada remaja sekolah. Saran: Sekolah diharapkan dapat melanjutkan program edukasi kesehatan mental secara rutin melalui kegiatan maupun bimbingan konseling agar siswa semakin memahami pentingnya menjaga kesehatan mental. Guru dan tenaga pendidik juga diharapkan lebih aktif dalam memberikan dukungan psikologis kepada siswa yang mengalami kecemasan akademik.